O portador de diabetes mellitus do município de Coromandel-MG numa perspectiva da promoção de saúde - Faria, Cleide Chagas da Cunha (2010)
This study aimed to characterize the health status of diabetes mellitus (DM) patients in the city of Coromandel, state of Minas Gerais, based on the theoretical perspective called "Field of Health". The descriptive cross-sectional approach was chosen. The study included 187 patients with diabetes mellitus type 1 (DM1) and diabetes mellitus type 2 (DM2). The sample was proportional to the number of DM patients registered and monitored in each of the five Units of Primary Health Care in the city. It was observed that 82.3% were females, 57.8% were over the age of 60 and 43.3% were married. Of the participants, 95.2% reported DM2, 41.5% showed changes in blood glucose levels, 55.1% had blood pressure above the recommended and 71.0% were overweight or obese. Pharmacological treatment with oral hypoglycemic agents was mentioned by 70.1%, and 31.6% reported hospitalization as a result of glycemic alterations. Of the total, 84.5% confirmed family life, 71.6% had family income below three minimum wages, and 75.4% were retired and 57.6% reported incomplete junior high school education. Regarding lifestyle, 47.1% avoided the consumption of sugar, preferring the use of sweetener; 88.2% reported drinking coffee daily; 90.9% reported not drinking alcohol; and 12.3% reported being smokers. Most 73.8% said they did not practice regular physical activity, and 36.9% reported having leisure and relaxation in their daily lives. Sleep alterations after diagnosis of DM were reported by 17.1%. Most of the sample group said they used the public health service for diagnosis, monitoring and treatment of DM. Daily use of medication was reported by 97.9% and attendance to meetings for diabetic patients was confirmed by 53.5% of the participants. Walking was the most cited way of locomotion to the Units of Primary Health Care, and 69% reported no difficulties in the monitoring and treatment of the disease. Family represented the main source of support 65.8% and 91.4% of participants reported having enough knowledge about DM. The results enabled the characterization of the reality investigated and raised some reflections on the condition of diabetic patients and the main determinants of risk factors, difficulties, problems and expectations faced by this population. They also emphasized the challenge of health professionals to make patients comply with a long-term treatment common in chronic conditions such as DM. Keywords: Diabetes Mellitus; Health Promotion; Field of Health.